Strategi Pembelajaran Role Playing dalam Meningkatkan Kepercayaan diri Siswa - Febriani Paudi; Oktavia Ngaito; Delvi Hulopi; Nindita Hulopi; Harinangsi Napu; Muh. Wahyuddin S. Adam (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
This research examines the impact of implementing role playing learning strategies on increasing students' self-confidence. The research results show that the role playing method has a positive influence, especially in increasing students' enthusiasm and self-confidence. However, there are several challenges that must be faced, such as time constraints, the need for more thorough preparation, and managing students who tend to be passive. In order to apply this method more effectively, there needs to be a solution to these obstacles, so that it can be applied optimally at various grade levels.eo Interaktif, Pemahaman Konsep IPS.